Potential use of dietary fibre from Hibiscus sabdariffa and Agave tequilana in obesity management. (March 2016) - Moyano, Gabriel; Sáyago-Ayerdi, Sonia G.; Largo, Carlota; Caz, Victor; Santamaria, Monica; Tabernero, Maria
Highlights: Rats consumed dietary fibre (DF) from H. sabdariffa (Hs) and A. tequilana (At). Animals fed Hs alone or combined with At (Mix) had lower body weight and adiposity. Plasma cholesterol and glucose were lower in Hs and Mix groups, and GLP1 was higher. Ground HS calyces in particular provide DF with potential anti-obesity uses. Abstract: The anti-obesity potential of dietary fibre (DF) from Hibiscus sabdariffa (ground calyces) and Agave tequilana (agave-fructans) as an additive in the feed of animals subjected to a high fat diet was examined. Over a 5-week period, the effects of each DF alone, and in combination, were examined with respect to food intake, weight gain, adiposity, plasma metabolic profile, appetite regulation and inflammatory biomarkers in white and brown adipose tissue. Supplementation with the ground H. sabdariffa calyces was associated with a reduction in body weight, adiposity, plasma total cholesterol and glucose. As novel findings, the addition of H. sabdariffa increased plasma GLP1, reduced proinflammatory cytokines in white adipose tissue and increased IL6 in brown adipose tissue; it therefore appears to be a promising source of functional DF. These effects were partially maintained when H. sabdariffa was supplied in combination with A. tequilana DF and were independent of appetite reduction.